Chapter Imparare dal lavoro. Formarsi e formare in ambito pedagogico - CUNTI, Antonia (Studies on Adult Learning and Education, 2022)
Professional practice is one of the preferred ways to produce new forms of learning. It can be configured as thinking in action, in which its implementation allows progressive adjustments of ideas that translate into doing. The use of educational pathways based on reflexivity can allow to consciously use practical experience to facilitate meaningful learnings, so that work situations become the chosen setting to act on reality and learn through it.